Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1302/0301-620x.98b10.bjj-2016-0483.r1
|View full text |Cite
|
Sign up to set email alerts
|

A survival analysis of 1084 knees of the Oxford unicompartmental knee arthroplasty

Abstract: AimsThe aim of this to study was to compare the previously unreported long-term survival outcome of the Oxford medial unicompartmental knee arthroplasty (UKA) performed by trainee surgeons and consultants. Patients and MethodsWe therefore identified a previously unreported cohort of 1084 knees in 947 patients who had a UKA inserted for anteromedial knee arthritis by consultants and surgeons in training, at a tertiary arthroplasty centre and performed survival analysis on the group with revision as the endpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 28 publications
(10 reference statements)
0
45
0
1
Order By: Relevance
“…Furthermore, single centre cohort studies, which used methods outside the scope of the present study, have shown that similar revision rates can be achieved for TKA and UKA 911 12 121 Hamilton and colleagues133 showed a reduced revision rate in those studies undertaken in high volume centres, although the strength of this evidence was weak. These results are considered to be related to the expertise and experience of the operating surgeons, producing better results, and their units having a higher threshold for revision surgery for unexplained pain and better postoperative support.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, single centre cohort studies, which used methods outside the scope of the present study, have shown that similar revision rates can be achieved for TKA and UKA 911 12 121 Hamilton and colleagues133 showed a reduced revision rate in those studies undertaken in high volume centres, although the strength of this evidence was weak. These results are considered to be related to the expertise and experience of the operating surgeons, producing better results, and their units having a higher threshold for revision surgery for unexplained pain and better postoperative support.…”
Section: Discussionmentioning
confidence: 52%
“…But recent literature has shown that the higher failure rates of UKA are associated with centres and surgeons performing low numbers of the procedure 89 10 11 12 Some evidence in the UK also suggests that UKA has significant advantages over TKA, with fewer serious medical complications, reduced mortality rates, faster recovery, and superior functional outcome 1314 15…”
Section: Introductionmentioning
confidence: 99%
“…Complication rates may also be higher when surgery is performed by trainees. For example, in 1 study of unicompartmental knee replacements, there were more reoperations for bearing dislocation in the trainee group, although there were similar TKR survival rates for attending and trainee surgeons .…”
Section: Discussionmentioning
confidence: 98%
“…From December 2016 to May 2017, twenty patients (20 osteoarthritic knees) scheduled to undergo Oxford medial UKA were included as the OA group. The inclusion criteria were the current indications for Oxford medial UKA:[ 4 7 ] isolated anteromedial OA producing pain, preserved full-thickness cartilage in the lateral compartment (joint space width >5 mm on valgus stress radiography), an intact anterior cruciate ligament (ACL), posterior cruciate ligament and medial collateral ligament (MCL), range of motion >90°, and varus and flexion deformity <15°. Age, obesity, and patellofemoral OA were not considered contraindications to surgery.…”
Section: Ethodsmentioning
confidence: 99%